2020
DOI: 10.1029/2019ea000923
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics and Synoptic Situations of Long‐Duration Heavy Rainfall Events Over North China

Abstract: The spatiotemporal characteristics of long-duration heavy rainfall (LDHR) events are statistically analyzed using hourly surface observations over central-southern North China during the warm seasons of 2011-2018, revealing pronounced variabilities in the frequency and amount of LDHR. Two accumulated rainfall peaks are found in the western (WHRR) and eastern (EHRR) regions of central-southern North China. The LDHR occurrence frequency decreases westward, and the peaks of the LDHR amount, frequency and intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In coastal areas, heavy rainfall events show the characteristics of long trajectories and wide extensions. The HRTs in NE and in N are mainly concentrated in the plains; in the NE, some of the HRTs follow the tributary valleys of the upper reaches of the Songhua River into the western side of the Da Hinggan Mountains, forming an area of concentrated HRTs in the valley areas of the Inner Mongolia Plateau (Figure 5a); in the N, Mount Taishan prevents the HRTs from moving further into northeast Shandong Province (Figure 6a), and the small‐scale area of concentrated HRTs formed in central Shanxi (Taiyuan) is contributed by persistent heavy rainfall events and prevented from moving northward by the Taihang Mountains (Kang et al ., 2020). Note that in Table 4, the standard deviation in spring of 4.34 (>1) in the N is much higher than that of other geographical divisions in spring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In coastal areas, heavy rainfall events show the characteristics of long trajectories and wide extensions. The HRTs in NE and in N are mainly concentrated in the plains; in the NE, some of the HRTs follow the tributary valleys of the upper reaches of the Songhua River into the western side of the Da Hinggan Mountains, forming an area of concentrated HRTs in the valley areas of the Inner Mongolia Plateau (Figure 5a); in the N, Mount Taishan prevents the HRTs from moving further into northeast Shandong Province (Figure 6a), and the small‐scale area of concentrated HRTs formed in central Shanxi (Taiyuan) is contributed by persistent heavy rainfall events and prevented from moving northward by the Taihang Mountains (Kang et al ., 2020). Note that in Table 4, the standard deviation in spring of 4.34 (>1) in the N is much higher than that of other geographical divisions in spring.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 shows that the spatial distribution areas of persistent heavy rainfall events in SW and NWE are more fixed in a year, so there will be more severe secondary hazards in the areas of concentrated HRTs. Many studies have demonstrated the close relationship between heavy rainfall events and the Taihang Mountains in N. The Taihang Mountains can effectively trigger and amplify mesoscale convective systems, leading to a concentration of heavy rainfall events on the eastern side of the mountains (Sun, 2005;Kang et al, 2020), which is generally consistent with the results in this study for the area of concentrated HRTs in N. In addition, note that in N the areas of concentrated HRTs are formed in Beijing during both summer and fall, which has the same temporal distribution of intense hourly rainfall events in the warm season as obtained by Li et al (2017b). In Taiwan, the areas of concentrated HRTs occur on the western side of the Central Range in spring and on the eastern side in fall, which is also corroborated by the seasonal study of extreme rainfalls in Taiwan by Henny et al (2021).…”
Section: Intra-annual Spatiotemporal Distribution Of Hrts Within Eigh...mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was contrary to our finding in the current study which probably concerns the different lengths of the data used in the studies. According to Kang et al (2020), extreme precipitation has been increasing in northern China for a long time. Regional differences have also been observed in some areas.…”
Section: Introductionmentioning
confidence: 99%
“…A large valley (named "V" here as in Figure 1), opening to east, is located at 38.4°N in the eastern Taihang Mountains, with more complex small-scale terrain on the mountain slopes. Many heavy rainfall events have been observed in valley "V" (Kang et al, 2020). Researchers tried to address the mechanisms responsible for the formation of MCSs, especially the impacts of the cold pool and terrain (Xia & Zhang, 2019;Xiao et al, 2017Xiao et al, , 2019.…”
mentioning
confidence: 99%